Descriptions of immature stages of Mythimna venalba (Moore) (Lepidoptera: Noctuidae) - Nur Athiqah Md Yusof,; Nur Azura Adam,; Marina Roseli, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
An outbreak of the cutworm Mythimna venalba (Moore) had caused a huge loss to rice farmers in 2011 in Peninsular Malaysia. This is due to the late identification of the larvae, which appears to be one of the rice pests. This study presents the morphological descriptions of immature stages of M. venalba including the larval chaetotaxy in detail. The larvae of M. venalba were collected from several rice fields in Peninsular Malaysia, and they were reared and maintained in the laboratory to establish a colony. Ten specimens of egg, larva, pupa and adult from the colony were selected and observed for morphological descriptions and larval chaetotaxy. The external morphology of the eggs, larvae, pupae, and adults was described and illustrated. Important taxonomic structures of the larvae were discussed. The absence of G2 seta in the cranial chaetotaxy and the L1 seta situated just slightly anterior to SD1 on the A9 segment of the abdominal chaetotaxy are good characters to distinguish M. venalba from other Mythimna species.